Navigating the complex realm of drug access in paediatric care. Issue 6 (20th March 2021) - Dean, Paige H; Carr, Roxane; Jensen, Chris; Strahlendorf, Caron
Abstract: A Drug Access Navigator (DAN) is a role that has been established in patient care settings with the goal of expediting the process by which patients obtain drugs through the Health Canada Special Access Program (SAP), individual drug companies' patient access programs (PAP), and public and private drug plans. In the paediatric setting, the process of accessing many drugs has grown increasingly complex. The majority of paediatric prescriptions involve 'off-label' drug use. This leads to an increased need for drug access through the SAP and/or PAPs and demonstrates that the need for a DAN may be particularly prominent in the paediatric population. To our knowledge, there is no evidence in the literature of a DAN functioning in a paediatric setting, though there is a demonstrable need. We plan to address this need by introducing a DAN for shared use at BC Children's Hospital, a paediatric tertiary care centre.